Factor Analyses and Validity of the Transplant Evaluation Rating Scale (TERS) in a Large Sample of Lung Transplant Candidates - Nöhre, Mariel; Paslakis, Georgios; Albayrak, Özgür; Bauer-Hohmann, Maximilian; Brederecke, Jan; Eser-Valeri, Daniela; Tudorache, Igor; de Zwaan, Martina (Frontiers in Psychiatry, 2020)
Objective: It is well known that the occurrence of mental disorders is more common in lung transplant candidates compared to the general population. After transplantation mental disorders may negatively affect quality of life, adherence to immunosuppressive medication as well as overall survival. Therefore, the identification of patients at risk is of utmost importance and in Germany pre-transplant psychosocial evaluation of the patients is required. To ensure high quality and comparability of these assessments, the use of psychometrically sound instruments is recommended. We applied the Transplant Evaluation Rating Scale (TERS), a broadly used expert interview. Two research groups have detected a two-factor structure of the TERS in different transplant samples; however, with slightly different results. The present study investigated which of the models would fit best in our sample of lung transplant patients. Additionally, we assessed convergent and predictive validity of the best fitting model to evaluate its clinical usefulness. Methods: Between 2016 and 2018 390 lung transplant candidates were evaluated and included in the study. The median age was 53 years and 54% were male. TERS interviews were conducted by trained medical doctors and psychologists. The participants completed questionnaires assessing quality of life and levels of depression and anxiety. Transplant- and disease-specific variables (lung disease, listing date, oxygen use) were taken from the patient charts. Confirmatory factor analysis was used to test the two proposed TERS-models in the present sample. Results: The two-factor structure of the TERS reported by Hoodin & Kalbfleisch fit our sample best, showing good psychometric properties. The factor “emotional sensitivity” was highly correlated with quality of life and measures of psychosocial health while the factor “defiance” correlated with obstructive lung disease and older age but not with quality of life. The two factors showed differential predictive validity with regard to time until listing and pulmonary-specific quality of life one year after transplantation. Conclusions: The two factors showed good psychometric properties, and differential convergent and predictive validity. However, further studies concentrating on the predictive value of the TERS and its factors regarding somatic outcomes (mortality, graft functioning) are required.